Electrocardiographic Changes in Elderly Patients During Endoscopic Retrograde Cholangiopancreatography - NG Kounis; GM Zavras; PJ Papadaki; SN Kouni; M Batsolaki; GV Gouvelou-Deligianni; C Markoglou; JA Goudevenos; CN Mallioris; C Kokkinis; K Kalokairinou; N Grapsas; et al. (Canadian Journal of Gastroenterology)
BACKGROUND: Cardiorespiratory complications may occur during gastrointestinal endoscopy, and elderly people seem to be more vulnerable to these complications during endoscopic procedures involving the manipulation of abdominal viscera. OBJECTIVES: To determine the incidence of cardiac arrhythmias, changes in oxygen saturation, heart rate and blood pressure during endoscopic retrograde cholangiopancreatography (ERCP) via Holter monitoring in elderly patients older than 70 years of age.